1995
DOI: 10.1016/0013-4694(94)00209-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific tonotopic organizations of different areas of the human auditory cortex revealed by simultaneous magnetic and electric recordings

Abstract: This paper presents data concerning auditory evoked responses in the middle latency range (wave Pam/ Pa) and slow latency range (wave Nlm/Nl) recorded from 12 subjects. It is the first group study to report multi-channel data of both MEG and EEG recordings from the human auditory cortex. The experimental procedure involved potential and current density topographical brain mapping as well as magnetic and electric source analysis. Responses were compared for the following 3 stimulus frequencies: 500, 1000 and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
240
4
18

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(292 citation statements)
references
References 54 publications
30
240
4
18
Order By: Relevance
“…Because of intrinsic limitations in MEG spatial resolution, MEG probably will not be able to provide substantial insight into which of these mechanisms, if any, may contribute to the observed deficit. However, there are components in the auditory evoked magnetic field that are generated by primary auditory cortex (Lutkenhoner et al, 2003, Pantev et al, 1995, Yvert et al, 2001. A future study focusing on such signals could therefore examine population frequency tuning of units that are more likely to have sharper tuning curves, at least in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Because of intrinsic limitations in MEG spatial resolution, MEG probably will not be able to provide substantial insight into which of these mechanisms, if any, may contribute to the observed deficit. However, there are components in the auditory evoked magnetic field that are generated by primary auditory cortex (Lutkenhoner et al, 2003, Pantev et al, 1995, Yvert et al, 2001. A future study focusing on such signals could therefore examine population frequency tuning of units that are more likely to have sharper tuning curves, at least in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological, neuromagnetic, and fMRI studies of auditory cortex in humans have shown that frequency sensitivity is bilaterally localized on the supratemporal plane, with low frequencies more lateral and anterior than high frequencies (Pantev et al, 1988(Pantev et al, , 1995Verkindt et al, 1995). However, some studies failed to find tonotopic mapping of N 100 and its magnetic counterpart N 100m and reported other factors, such as latency, to be important (Roberts and Poeppel, 1996;Stufflebeam et al, 1998;Lutkenhoner et al, 2003).…”
Section: Frequency Mapping In the Auditory Systemmentioning
confidence: 99%
“…Several studies have suggested that N1m originates from HeschlÕs Gyrus (Elberling et al, 1982;Reite et al, 1994); but the secondary auditory areas in the supratemporal plane are another possibility (Pantev et al, 1995;Lütkenhö ner and Steinsträter, 1998). It would be useful to compare the location of these activation sites with cyto-architectonic data in order to assess whether frequency-dependent activated areas are located in the same physiologically defined field, which would reflect tonotopy, or in separate fields, which would not point to any tonotopic organization (Schö nwiesner et al, 2002).…”
Section: Tonotopic Organization Of the Auditory Cortexmentioning
confidence: 99%